Subduction and rifting ‒ reflect of oscillatory tectonic processes on boundaries of the lithosphere segments in the probable-deterministic gravity models - Petrishchevsky, A. M. (Litosfera (Ekaterinburg. Online), 2025)
Research subject. Convergent boundaries of the Euroassian, North American, Pacific lithosphere plates and protooceanic plate of the South China Sea on the Eastern Asia. Aim. On the base of tectonic analysis of 3D rheological gravity models compared with another geologic-geophysical data to study deep structures in zones of joint of lithosphere plates and to define space-time relations between subducton and rift structures. Material and Methods. Land and seas gravity measurements on the Russian territory and Land Gravity Data.bgi.omp.obs-mip.fr, model: EGM08_CBA_global_2190_2.5m on the territories of South East China and Sea of Japan were used. Main method of research is the gravity method for modeling of rheological properties of the crust and upper mantle by distributions of the density contrast (differentiation) of geological media (authors method). Results. Analysis of 3D distributions of density inhomogeneities in a tectonosphere of the North East Russia, Japan Sea Region, Sikhote Alin and South East China is carried out, as a result of which in the Eastern margin of Asia identical traces of tectonic processes on boundaries of the lithosphere plates, reflected their directed-oscillatory character are revealed. Traces of the subduction processes has been founded in a shape of inclined rigid sheets (slabs) reflected by maximums of the density contrast and moved under continental margin and island arcs. However the subduction was not constant in time and periodically was interrupted by kickbacks and gaps of subducting slabs under influence of rifting and transform-shift processes. In time the rifts and attendant their shifts have been displaced in a direction from autochthonous to allochthonous segments: in the North East Asia from North Asian Craton to North American plate, on the Eastern Asia – from the continent to Pacific, and on the South East Asia – from the South China Sea Plate to Yangtze plate. Conclusions. Revealed features of a structure and geodynamic evolution of convergent zones are universal characteristics of upper rigid layers of the Earth (crust and lower lithosphere) moved above subcrustal viscous layer and astenosphere under influence of the oscillation tensions, caused, most likely, by deviation of the Earth rotation parameters. In all of four areas identical sequence of subductional and rifting processes has been revealed. A subduction accompanied by thrusting of the upper crust layer over autochthonous segments was repeatedly interrupted by gaps of crustal and lithosphere sheets and a formation of stretch-shift structures. Sudduction is not main and defining process in the convergent boundaries of lithosphere plate, bat represents a privet element of the oscillatory tectogenesis.